Primary intraosseous atypical inflammatory meningioma presenting as a lytic skull lesion: Case report with review of literature - Sangita Bohara; Swapnil Agarwal; Nita Khurana; P N Pandey (Wolters Kluwer Medknow Publications, 2016)
Primary extradural meningiomas of the skull comprise 1% of all meningiomas, and lytic skull meningiomas are still rarer and are said to be more aggressive. We present a case of 38-year-old male with an extradural tumor which on histopathological examination showed features of inflammatory atypical meningioma (WHO Grade II). The intense inflammatory nature of osteolytic primary intraosseous meningioma has not been reported before. This entity deserves special mention because of the need for adjuvant therapy and proper follow-up.